Pengaruh Kepemimpinan Transformasional Kepala Sekolah Terhadap Perubahan Organisasi Sekolah Dasar - Windasari Windasari; Erny Roesminingsih; Syunu Trihantoyo (Kelola: Jurnal Manajemen Pendidikan, 2022)
Today's global world changes encourage schools to start making organizational changes. School leaders are expected to be able to develop competitive strategies and create organizational changes in schools. This study aims to determine the effect of transformational leadership on organizational change in elementary schools. This study uses a quantitative approach using simple linear regression test data analysis techniques. The independent variable in this study is the principal's transformational leadership while the dependent variable is organizational change. The sample was 396 respondents with simple random sampling method. The results of the study indicate that transformational leadership has an effect on organizational change in elementary schools. Organizational changes in elementary schools by 60% are influenced by the principal transformational leadership.